Iron stores in regular blood donors in Lagos, Nigeria - Adediran A; Uche EI; Adeyemo TA; Damulak OD; Akinbami AA; Akanmu AS (Journal of Blood Medicine, 2013)
Adewumi Adediran,1 Ebele I Uche,2 Titilope A Adeyemo,1 Dapus O Damulak,3 Akinsegun A Akinbami,4 Alani S Akanmu1 1Department of Hematology and Blood Transfusion, University of Lagos, Lagos, Nigeria; 2Department of Hematology and Blood Transfusion, Lagos University Teaching Hospital, Lagos, Nigeria; 3Department of Hematology and Blood Transfusion, Jos University Teaching Hospital, Jos, Nigeria; 4Department of Hematology and Blood Transfusion, Lagos State University, Ikeja, Nigeria Background: Apart from challenging the bone marrow to increase its red cell production, thereby producing more blood for the donor, regular blood donation has been shown to have several benefits, one of which is preventing accumulation of body iron which can cause free radical formation in the body. This study was carried out to assess body iron stores in regular blood donors. Methods: A total of 52 regular (study) and 30 first-time (control) volunteer blood donors were studied prospectively. Twenty milliliters of venous blood was drawn from each subject, 5 mL of which was put into sodium ethylenediamine tetra-acetic acid specimen bottles for a full blood count, including red blood cell indices. The remaining sample was allowed to clot in a plain container, and the serum was then retrieved for serum ferritin, serum iron, and serum transferrin receptor measurement by enzyme-linked immunosorbent assay. Results: Mean hemoglobin and packed cell volume in the study group (13.47 ± 2.36 g/dL and 42.00 ± 7.10, respectively, P = 0.303) were not significantly higher than in the control group (12.98 ± 1.30 g/dL and 39.76 ± 4.41, respectively, P = 0.119). Mean serum ferritin was 102.46 ± 80.26 ng/mL in the control group and 41.46 ± 40.33 ng/mL in the study group (P = 0.001). Mean serum ferritin for women in the study group (28.02 ± 25.00 ng/mL) was significantly lower than for women in the control group (56.35 ± 34.03 ng/mL, P = 0.014). Similarly, men in the study group had a lower mean serum ferritin (48.57 ± 45.17 ng/mL) than men in the control group (145.49 ± 87.74 ng/mL, P = 0.00). The mean serum transferrin receptor value was higher in the study group (1.56 ± 0.88 µg/mL) than in the control group (1.19 ± 0.38 µg/mL, P = 0.033). Conclusion: These findings suggest that hemoglobin concentration, packed cell volume, and serum iron levels are not significantly affected by regular blood donation and that regular blood donors appear to have reduced iron stores compared with controls. Keywords: blood donors, hemoglobin, serum ferritin, serum iron, transferrin receptors